2018
DOI: 10.1021/acs.jpclett.8b03185
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transport with Mobility, μ > 86 cm2/(V s), in a 74 nm Long Polyfluorene

Abstract: The mobility of charges on conjugated polymers is a fundamentally important feature of these materials, but most fall far short of transport that might lead one to call them "molecular wires". A commonly identified bottleneck is flexible dihedral angles between repeat units. Here we find a very high mobility, μ > 86 cm 2 /(V s), for electrons attached to polyfluorene polymers in isooctane, despite the presence of varied dihedral angles. The present data suggest that interactions with the surrounding medium may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Nonpolar solvents make an electron more delocalized, extending into the electron donor moiety, which likely leads to faster electron transport in the uneven electronic surface. This, in turn, supports the idea put forth in a recent study by Cook et al that the interaction with the surrounding medium can be the dominant factor in determining charge mobilities …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Nonpolar solvents make an electron more delocalized, extending into the electron donor moiety, which likely leads to faster electron transport in the uneven electronic surface. This, in turn, supports the idea put forth in a recent study by Cook et al that the interaction with the surrounding medium can be the dominant factor in determining charge mobilities …”
Section: Discussionsupporting
confidence: 88%
“…This, in turn, supports the idea put forth in a recent study by Cook et al that the interaction with the surrounding medium can be the dominant factor in determining charge mobilities. 42…”
Section: Discussionmentioning
confidence: 99%
“…Pulse radiolysis time-resolved microwave conductivity measurements on various polymers by Grozema et al have suggested transport is unhindered over small length scales and the mobility can be comparable to that of inorganic semiconductors . Cook and co-workers have recently reported charge mobility as high as 86 cm 2 /(V s) along a single polyfluorene chain employing a pulse radiolysis technique . Over the past few years, experimental and theoretical studies have indicated that high μ values can be achieved in novel conjugated polymer architectures despite poor interchain registry. , These disordered or even seemingly amorphous, high-mobility, donor–acceptor type conjugated copolymers have emerged with charge mobility greater than 1 cm 2 /(V s), thanks to their extended persistence lengths associated with the high polymer backbone rigidity, and extended conjugation via fused aromatic rings .…”
mentioning
confidence: 99%
“…19 Cook and co-workers have recently reported charge mobility as high as 86 cm 2 /(V s) along a single polyfluorene chain employing a pulse radiolysis technique. 20 Over the past few years, experimental and theoretical studies have indicated that high μ values can be achieved in novel conjugated polymer architectures despite poor interchain registry. 21,22 These disordered or even seemingly amorphous, high-mobility, donor−acceptor type conjugated copolymers have emerged with charge mobility greater than 1 cm 2 /(V s), 23−25 with the high polymer backbone rigidity, and extended conjugation via fused aromatic rings.…”
mentioning
confidence: 99%
“…In this experiment we did not see any systematic evidence of that, with F 5 , F 10 , and pF all showing approximately the same shift in redox potential due to ion-pairing suggesting no enhancement in charge escape. Such effects may require an electric field parallel to the chain 52 or require a lower polarity environment where the intramolecular charge mobility would be higher 53 than in THF. 54 Even the occurrence of ion pairing with ΔG°d(F x −• ,TBA + ) = 162−222 meV probably implies that the TBA + has suppressed the electron mobility.…”
Section: The Journal Ofmentioning
confidence: 99%